TIDE: adjuvant tislelizumab plus donafenib combined with transarterial chemoembolization for high-risk hepatocellular carcinoma after surgery: protocol for a prospective, single-arm, phase II trial - Qi, Weili; Peng, Wei; Qi, Xin; Qiu, Zhancheng; Wen, Tianfu; Li, Chuan (Frontiers in Oncology, 2023)
Background: The high recurrence rate of hepatocellular carcinoma (HCC) after surgery negatively affects the prognosis of patients. There is currently no widely accepted adjuvant therapy strategy for patients with HCC. A clinical study of effective adjuvant therapy is still needed. Methods: In this prospective, single-arm, phase II clinical trial, an adjuvant regimen of donafenib plus tislelizumab combined with transarterial chemoembolization (TACE) will be used to treat enrolled HCC patients after surgery. Briefly, patients newly diagnosed with HCC by pathological examination who underwent curative resection and had a single tumor more than 5 cm in diameter with microvascular invasion as detected by pathological examination are eligible. The primary endpoint of the study is the recurrence-free survival (RFS) rate at 3 years, and secondary endpoints are the overall survival (OS) rate and the incidence of adverse events (AEs). The planned sample size, 32 patients, was calculated to permit the accumulation of sufficient RFS events in 3 years to achieve 90% power for the RFS primary endpoint. Discussion: Vascular endothelial growth factor (VEGF) and programmed cell death protein 1 (PD-1)/programmed cell death ligand 1 (PD-L1) pathways regulate the relevant immunosuppressive mechanisms of HCC recurrence. Our trial will evaluate the clinical benefit of adding donafenib plus tislelizumab to TACE in patients with early-stage HCC and a high risk of recurrence. Trial Registration: Chinese Clinical Trial Registry Identifier: ChiCTR2200063003. Date of registration: August 27, 2022.